2020
DOI: 10.1371/journal.pone.0237941
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant beef cow’s nutrition and its effects on postnatal weight and carcass quality of their progeny

Abstract: A systematic review (SR) and meta-analysis (MA) were performed to evaluate the effects of different energy levels (metabolizable energy, ME) and crude protein (CP), supplied to pregnant cows, on weight of their progenies at 60 (BW60), 100 (BW100), 180 (BW180) and 205 (BW205) days of age, average daily gain (ADG), and weight, age, loin eye area (LEA), marbling and fat thickness (FT) at slaughter. The SR was performed on two electronic databases. The MA for random effects was performed for each response variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 66 publications
0
10
0
2
Order By: Relevance
“…Our findings demonstrated that in most of the studies available, treatments were applied from mid to late gestation. Consistently, Zago et al [ 9 ] also verified the low availability of fetal programming and gestational nutrition studies focused on the first trimester of pregnancy. Herein, studies that contemplate the effects of maternal nutrition during early gestation were further explored.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Our findings demonstrated that in most of the studies available, treatments were applied from mid to late gestation. Consistently, Zago et al [ 9 ] also verified the low availability of fetal programming and gestational nutrition studies focused on the first trimester of pregnancy. Herein, studies that contemplate the effects of maternal nutrition during early gestation were further explored.…”
Section: Discussionmentioning
confidence: 58%
“…Maternal nutrition affects the nutrient partitioning [ 3 ] and acts as a signal-promoting epigenetic modification [ 4 ], which causes alterations in gene expression [ 5 , 6 , 7 ]. Thereafter, in the postnatal life, these effects induced by the intrauterine conditions may be expressed as alterations in the offspring growth [ 8 , 9 ], in the relative masses of muscle and adipose tissue (lean-to-fat ratio) [ 10 ], and the meat yield [ 11 ] and quality [ 12 ]. Therefore, a broader understanding regarding the effects of maternal dietetic manipulations during gestation on the offspring is crucial to produce herds with the desired quality.…”
Section: Introductionmentioning
confidence: 99%
“…These changes in progeny performance can be permanent and can be observed in the adult life of the animal, although they are more noticeable in the initial months of the offspring's life (Klein et al, 2021b). In a meta-analytic study, Zago et al (2020) observed that the progeny of cows that consumed energy and protein above the maintenance requirements showed greater weight gain at finishing, were slaughtered 5.5 days earlier and presented meat with a higher marbling content, an aspect much appreciated by consumers.…”
Section: Resultsmentioning
confidence: 99%
“…A subnutrição durante a gestação causa condições subótimas ao ambiente uterino materno, o que pode influenciar positiva ou negativamente o desenvolvimento de órgãos e tecidos fetais e levar a impactos ao longo da vida no desempenho da progênie (Broadhead et al, 2019). Por exemplo, Zago et al (2020) observaram em sua meta-análise, que a progênie de vacas que consumiram energia e proteína acima das exigências de mantença apresentaram maior ganho de peso na terminação, e produziram uma carcaça com maior teor de marmoreio e gordura de cobertura, aspectos apreciados pelos consumidores. Do mesmo modo que a restrição nutricional afeta a oferta de nutrientes para o feto, o excesso de nutrientes, ou a superalimentação da vaca gestante, também interfere na formação fetal.…”
Section: Programação Fetal E As Consequências Na Progênieunclassified
“…Os autores complementam que essa diferença persistiu até o desmame e abate, e que os novilhos de vacas suplementadas tendem a ganhar mais peso após a colocação no confinamento em comparação com novilhos de vacas não suplementadas. Em estudo meta-analítico, Zago et al (2020) observaram que os novilhos cujas mães consumiram proteína e energia acima dos níveis exigidos durante o terceiro trimestre de gestação foram abatidos 5,5 dias antes em comparação com outros novilhos. Este resultado é reflexo do melhor desempenho da progênie de vacas bem nutridas na gestação, uma vez que conseguem potencializar a utilização de nutrientes em sistemas intensivos de produção.…”
Section: Implicações No Desempenho Da Progênieunclassified